Sulitar Irrigation System: Struggle from Poverty to Prosperity - Rijal, Krishna Prasad (Hydro Nepal: Journal of Water, Energy and Environment, 2015)
Nepal has glorious history with tens of thousands of self sustainable farmer managed irrigation systems, which accounts for about two third of total irrigated area in the country. Sulitar Irrigation System, located in Chitwan district of Nepal and constructed almost two decades ago, is one of them. The farmers have been relentlessly working for construction, maintenance, repair and operation of the system with wider community participation. Participation is not only limited to the field level but also extends to crafting of rules and regulation pertaining to the governance of the system. Participatory approach adopted in this system has fostered transparency and accountability in the management entity with a sense of ownership and self responsibility as an asset embraced by water users. In addition, effective system of resource mobilization for Operation and Maintenance (O & M) is appreciable. Their working culture of participation, purposefulness and integrity has drawn in huge amount of internal as well as external resources to the project. Efficient networking with other organizations has led to profound resource mobilization, leadership sharing and a buildup of strong social capital. They are also well aware of the sustainability of the system and pre-requisites for it. Resource generation and O & M of the system have been institutionalized for its durability and long-term sustainability. Fundamental requirement for an irrigation system is the impact made by the system on the agriculture and livelihood of the people within the command area. Subsistence based agriculture prevailing before the service of irrigation system has now advanced to crop intensification and crop diversification paving the way for commercialization. Food security in the community has been enhanced and poor livelihood of common people has been transforming towards prosperity. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 17, July 2015